Prediction of active marker of seabuckthorn polysaccharides for prevention and treatment of cervical cancer and mechanism study - Feng, Xuehua; Song, Zurong; Tao, Ali; Gong, Panpan; Pei, Wenqing; Zong, Rumin (Frontiers in Nutrition, 2023)
Objective: To predict the target of Seabuckthorn polysaccharides in the prevention and treatment of cervical cancer, and to explore its multi-target and multi-pathway mechanism. Methods: TCMSP database was used to predict the potential targets of polysaccharide active components. Cervical cancer related targets were obtained from the GeneCards database. The intersection of active ingredient targets and disease targets was obtained by Venn diagram. Cytoscape3.6.0 software was used to construct the Polysaccharide composition-Target-Disease Network and Protein-Protein Interaction Networks（PPI）. Cytoscape3.6.0 software was used for visualization and network topology analysis to obtain core targets. Kyoto encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) were analyzed using Metascape database. SailVina and PyMOL software were used for molecular docking to verify binding strength. Results: A total of 15 core targets were obtained for cervical cancer. These targets are significantly enriched in HIF-1 signaling pathway, Galactose metabolismh, EGFR tyrosine kinase inhibitor resistance, growth factor receptor binding, carbohydrate binding, protein homodimerization activity and other GO and KEGG entries; Molecular docking showed that ADA and GLB1 were well bound to Glucose, D-Mannose, and Galactose. Conclusion: The effect of seabuckthorn polysaccharides on the prevention and treatment of cervical cancer is characterized by multi-component, multi-target and multi-pathway, which provides scientific basis for further research on the activity of seabuckthorn polysaccharides.